Serahsi’nin aile hukuku hükümlerinin gayelerine ilişkin analizleri - Şenkardeşler, Hatice Boynukalın (My University, 2009)
SERAHSÎ’NİN AİLE HUKUKU HÜKÜMLERİNİN GAYELERİNE İLİŞKİN ANALİZLERİ Araştırmamızda ictihad faaliyeti açısından önem arz eden, Şârî‘in gayelerine vukûfiyet düşüncesine, Hanefî mezhebi bilginlerinin hukuk mantığında ayrılan yerin tespit edilmesine çalışılmıştır. Tezimizin düzey ve hacmi açısından geniş bir furû fıkhı külliyâtına sahip bulunan Hanefî mezhebi literatürünün tamamını taramanın zorlukları göz önünde bulundurularak konumuz Hanefî furû fıkhı dendiğinde ilk akla gelen temel yapıtlardan olduğu tartışma götürmez olan Serahsî’nin el-Mebsût adlı eserindeki aile hukukuyla ilgili hükümlerle sınırlandırılmıştır. Tüm hukuk sistemlerinde olduğu gibi İslam hukukunda da önemli ve özel bir yeri bulunan aile hukuku ile ilgili hükümlerin taranması suretiyle bu hükümlerin arkasındaki aslî gayelerin yanında pek çok tâlî gayenin de tespit edilmesi mümkün olmuştur. Bu tespitlerimiz sonucunda İslam aile hukukunun gerek aslî gerekse tâlî gayelerinin tamamının -İslam Hukukunun genel olarak da nihâî gayesi olan- insanların faydasını (maslahat) te’min ve onlardan zararı uzaklaştırma düşüncesi üzerine temellendirildiğini söylemek mümkündür. Gelişen sosyal hayatla birlikte ortaya çıkan yeni meselelerin çözülmesi bakımından Şârî‘in gayelerinin bilinmesinin müctehid açısından sağlayacağı yararın yadsınamaz olduğu gerçeğinden hareketle, fıkhın her dalında bu gayelerin tespiti yönünde çalışmaların yapılması gerektiği kanaatindeyiz.

SARAKHSI’S ANALYSES CONCERNING THE OBJECTIVE OF LAWS RELATING TO FAMILY LAW In our work, the distinguished place of the notion that the Lawgiver’s objectives are known only through the vehicle of revelation (wukufiyet) in the legal logic of the Hanafi school and from the point of view of the activity of ijtihad has been established. When the subject of the work as being that of Hanafi substantive law is said, the first among the basic works that occurs to the mind is the undisputed work of Sarakhsi entitled the Mabsut. Taking into consideration the difficulty of combing through the vast and wide universe of substantive law which is found in all of the literature of the Hanafi school, and due to the restricted level and volume of this thesis, this work is confined to the rulings in the Mabsut related to family law. As is the case in all legal systems, in Islamic law also, when combing through the rules related to family law, which occupies an important and special place in law, it is possible to determine the primary objectives lying behind the law and more or less secondary objectives that accompany the primary ones. As a result of this finding, it is possible to firmly establish that Islamic family law’s objectives, both the primary and secondary ones – are to ensure and guarantee the well-being (maslahat) of the human being. Such well-being fits with the general and overall final objective of Islamic law which is the avoidance of harm. From the perspective of finding solutions to new issues which arise in modern times along with the developing of social life, the benefit of knowing the Lawgiver’s purpose for the jurist is undeniable. Consequently, the completion of such work is necessary in order to establish and bring to light the Lawgiver’s objectives in all the branches of Islamic law.
Keywords: Aile Hukuku; İslam Dini; İslam Hukuk